2007
DOI: 10.1111/j.1741-6248.2007.00091.x
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Development of a Family Business Self-Efficacy Scale: A Resource-Based Perspective

Abstract: Given the importance of succession planning in family‐owned businesses, our research is focused on identifying the key dimensions that could comprise a family business self‐efficacy scale. We employed an explorative qualitative research methodology by querying a group of family business presidents to describe the skills critical for success. Using a resource‐based perspective and relevant family business succession literature, we organized this feedback into a framework depicting the key challenges associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 55 publications
(81 reference statements)
0
52
0
Order By: Relevance
“…DeNoble et al (2007) offer guidance on how to modify existing entrepreneurial self-efficacy scales for their greater applicability in the family business context. For instance, items in the entrepreneurial self-efficacy scale of Chen, Green & Crick (1998) can be supplemented with additional items related to managing family and stakeholder relationships, skills particularly important in the effective leadership and management of family firms (DeNoble et al, 2007). As for family business commitment, the scale of Allen and Meyer (1990) has been modified for use in family firms (Dawson et al, 2015).…”
Section: Temporal Contingencies and Considerations A Theoretical Extmentioning
confidence: 99%
See 2 more Smart Citations
“…DeNoble et al (2007) offer guidance on how to modify existing entrepreneurial self-efficacy scales for their greater applicability in the family business context. For instance, items in the entrepreneurial self-efficacy scale of Chen, Green & Crick (1998) can be supplemented with additional items related to managing family and stakeholder relationships, skills particularly important in the effective leadership and management of family firms (DeNoble et al, 2007). As for family business commitment, the scale of Allen and Meyer (1990) has been modified for use in family firms (Dawson et al, 2015).…”
Section: Temporal Contingencies and Considerations A Theoretical Extmentioning
confidence: 99%
“…While some entrepreneurial skills are needed, research on attributes that are important for the success of nextgeneration members engagement suggests this context calls for a unique set of capabilities (Chrisman, Chua, & Sharma, 1998). Taking over a family firm's leadership, next-generation members have the added responsibility of managing and maintaining both family and business relationships, gaining buy-in and support from non-family employees and other key stakeholders (DeNoble, Ehrlich, & Singh, 2007;Tabor, Chrisman, Madison, & Vardaman, 2018). That is, they need both formal and cultural competencies (Hall & Nordqvist, 2008).…”
Section: Social Cognitive Theory and Next-generation Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…being a leader and communicator; (6) building up a professional network; (7) commercializing a new idea or development; and (8) successfully managing a business. The eight items were developed from previous studies of self-efficacy and innovation (Chen, Greene, and Crick 1998;Zhao 2005;Kickul et al 2009;DeNoble, Ehrlich, and Singh 2007). The measuring scale was from 1 (very low competence) to 7 (very high competence).…”
Section: Methodsmentioning
confidence: 99%
“…Past studies have shown that individuals with high scores on this sub skill have higher intentions of establishing enterprises, exert more effort into the enterprise formation process and succeed at a higher rate than those that score low. Several measurement tools for this construct have been developed (Chen, Greene, & Crick, 1998;DeNoble, Ehrlich, & Singh, 2007;McGee et al, 2009). Bandura (1986) conceptualized the self-efficacy construct in his social cognitive theory (SCT) and surmised that there is a reciprocal relationship between one's behavioral, cognitive, and environmental consequences so that perception of positive consequences reinforces similar behavior in the future while perceived negative consequences discourages similar behavior.…”
Section: Introductionmentioning
confidence: 99%